Oscillator driven central pattern generator (CPG) system for animating quadruped locomotion - Bhatti, Zeeshan (2015)
This thesis work proposes a unique framework for generating quadruped animation of various locomotion gaits and patterns using a dual layer of hybrid mathematical model. Animation has become an integral part of everyday entertainment industry from games, movies, television to scientific research and development. Creating animation of quadrupeds is an extremely long and tedious process through key-framing. Motion capture data for multiple gait types is not so commonly available for quadruped animals and this processes itself is expensive both financially and in skill required. In this research, a two tier based procedurally generated animation framework is proposed which is able to simulate various quadruped locomotion gaits using procedural programming techniques. Initially a detailed motion analysis study was done to understand the biomechanics of quadruped gait patterns and footfall timing. The gait types which were studied consists of walk, trot, gallop, canter, pace, and rack for 4 primary animals including Horse, Lion, Tiger and Cat. The basic quadruped skeletal model is automatically rigged using procedural rigging techniques and custom manipulator are incorporated for higher level control of generated simulation by the user. The animation system model consists of a oscillator based Central Pattern Generator (CPG) which is able to produce couple leg oscillation derived through user controlled parameters, producing in-phase and out-of-phase leg swing motion curves. Each leg has a separate CPG unit that is able to generate and control the swing and stance phases of each gait cycle with couple oscillation, having a time shift in correspondence to each leg, in a permuted symmetry. The dynamic motion is calculated independently for each body part with user interaction and control over the speed, frequency and oscillation of body parts individually through a UI, during runtime, for high divergence control of the simulation. The user can manipulate the simulation parameters for leg impact phases and duration at runtime and our system will automatically adjust the motion gaits and transitions between each gaits at runtime. Our procedural model for animating quadrupeds is able to generate various locomotion gaits with varying speed and footfall pattern dynamically. The various gaits produced by the CPG system are, walk, trot, gallop, canter, pace, pronk and rack, along with turning around in any specified direction, moving up on a hill or coming down from uneven terrain, crouching and crawling. Various gait and footfall timing test are performed to test and validate the motion, along with a study of user's perception test to determine a Visual Mean Opinion Score (VMOS) of the believability and accuracy of the generated animation with statistical significance. The test and validation of the generated motion gaits shows that the system accuracy and believability rate is at 84% with VMOS of 4.1 out of 5, which is a very pleasing and satisfactory outcome for this generic animation framework. The potential application area of this research work could be in CGI Movies, 3D Animated Movies, Game Animations, Special Effects, Character Simulations and Virtual Reality applications